Generative Artificial Intelligence Systems in the Fight Against Corruption: Potential, Threats and Prospects for Ukraine - Dumchikov, Mykhailo; Maletova, Olha (International Journal of Criminology and Sociology, 2025)
Corruption remains one of Ukraine’s most pressing challenges, undermining the rule of law, hindering economic development, and eroding public trust in state institutions. In the contemporary digital transformation era, generative Artificial Intelligence (AI) systems present new opportunities for combating corruption through automated solutions for financial flow analysis, anomaly detection, and corruption risk assessment. However, deploying such technological systems raises significant legal, ethical, and technical concerns. This article analyses the potential and challenges of applying generative AI systems in Ukraine’s anti-corruption policy. Through comparative analysis of international experience, the study identifies effective methods for implementing AI in Ukraine’s law enforcement and governance practices, considering the country’s legislative framework and political context. The research examines risks associated with AI implementation, including algorithmic manipulation, cybersecurity threats, data protection concerns, and ethical challenges. The authors propose recommendations for adapting AI technologies to Ukraine’s anti-corruption efforts, including developing regulatory frameworks, introducing algorithmic accountability, implementing ethical AI standards, and strengthening international cooperation. The findings demonstrate that, with proper regulation and oversight, generative AI can enhance government transparency and reinforce the rule of law in anti-corruption efforts.